SHALAT JAMA’AH MEMUPUK NILAI SOLIDARITAS - Saiful Huda (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2018)
The quality of formal education institutions in Indonesia has been questioned again in effectiveness as more and more cases of fights are heard among students. Conversely, from behind the world of education Islamic boarding schools hardly heard the same case. Of course this is very interesting to study more deeply because surely in the system and method of Islamic boarding schools there are educational materials that are able to form a noble character.The success of Islamic boarding schools to print students who are moral and virtuous cannot be separated from one aspect of the educational material of Islamic boarding schools in the form of congregational prayers performed by santri sincerely. Prayer jama'ah and the aurad reading afterwards diistiqam together together every five times a day and have a very significant role in shaping the mentality of the child has a soul of high solidarity.The momentum of togetherness in congregational prayer is like a therapy. Jama'ah prayer can foster an atmosphere that freezes into liquid. Through this